The Development of Self-Knowledge in Plato’s Philosophy - Ortíz de Landazuri, Manuel C. (Logos. Anales del Seminario de Metafísica, 2015)
The aim of this paper is to examine how the Greek motto γνῶθι σεαυτόν plays a central role in Plato’s philosophy in order to show how ethics and knowledge go hand in hand in his model of παιδεία. The question of self-knowledge is a practical and theoretical task in life which is developed implicitly in his dialogues, it is for this reason that i examine some passages of the Charmides, Alcibiades I, Phaedo and Republic in order to show how Plato discovers the human interiority (Phaedo) and how self-knowledge is refined and articulated with the tripartition of the soul in the Republic.